Stability and Resilient Modulus of Porous Asphalt Incorporating Steel Fiber - N. A. M., Radzi; K. A., Masri; Putra Jaya, Ramadhansyah; N. E., Jasni; A. K., Arshad; J., Ahmad; Nordiana, Mashros; Haryati, Yaacob (IOP Publishing, 2020)
Porous Asphalt (PA) is known as a highly permeable asphalt surface that design to be permeable pavements for stormwater control and reduce the stormwater runoff. However, the structure is subjected to damage from cracking, rutting, stripping, and rapid aging under the effects of repeated vehicle loading, hot climates, and heavy rainfall. To overcome this, PA needs to modify using high tensile strength like steel fiber. Thus, this study aims to evaluate the performance of PA with the addition of steel fiber and overcome the issue that is related to PA. A mixture contains varying percentages of steel fiber were assessed to check which samples gives the best performance as per the requirement by using laboratory tests which are LA Abrasion, Resilient Modulus, Marshall Stability, and Density. The results show that the additions of 0.6% steel fiber give the lowest value of abrasion, while 0.5% fiber content contributes the highest value of Resilient Modulus and Marshall Stability respectively. PA mixtures modified with steel fiber produce the performance enhancement of PA as a road surfacing material. It is concluded that the asphalt mixtures containing steel fibers could increase the stability and strength of the mix.